Antimicrobial use and aetiology of bloodstream infections in critically ill patients during early stages of SARS-CoV-2 pandemic. Issue 4 (December 2022) - Torrecillas, Miriam; Gumucio, Victor Daniel; Padullés, Ariadna; Tubau, Fe; Marco, Daniel; Shaw, Evelyn; Fernández-Huerta, Miguel; Maisterra, Krystel; Grau, Inmaculada; Petito, Melanie Maria; Berbel, Dàmaris; Puig-Asensio, Mireia; et al.
Summary: Background: During early stages of COVID-19 pandemic, antimicrobials were commonly prescribed. Aim: To describe clinical, microbiological and antimicrobial use changes in bloodstream infections (BSI) of ICU patients during the first wave of COVID-19 pandemic compared to pre-COVID-19 era. Methods: Observational cohort study of patients admitted to ICU of Bellvitge University Hospital was conducted during the COVID-19 pandemic (March-June 2020) and before COVID-19 pandemic (March-June 2019). Differences in clinical characteristics, antimicrobial consumption and incidence and aetiology of BSI were measured. Findings: COVID-19 patients had significantly less comorbidities with obesity the only risk factor that increased in frequency. COVID-19 patients more frequently required invasive supportive care measures, had longer median ICU stay and higher mortality rates. The incidence of BSIs was higher in COVID-19 period (RR 3.2 [95%CI 2.2–4.7]), occurred in patients who showed prolonged median ICU stay (21days) and was associated with high mortality rate (47%). The highest increases in the aetiological agents were observed for AmpC-producing bacteria (RR 11.1 [95%CI 2.6–47.9]) and non-fermenting rods (RR 7.0 [95%CI 1.5–31.4]). The emergence of bacteraemia caused by Gram-negative rods resistant to amoxicillin-clavulanate, which was used as empirical therapy during early stages of the pandemic, led to an escalation towards broader-spectrum antimicrobials such as meropenem and colistin which was also associated with the emergence of resistant isolates. Conclusions: The epidemiological shift towards resistant phenotypes in critically ill COVID-19 patients was associated with the selective use of antimicrobials. Our study provides evidence of the impact of empirical therapy on the selection of bacteria and their consequences on BSI over the subsequent months.